The mode of public university education curriculum implementation in Oyo state (2012)
This study investigated the mode of higher education curriculum implementation among higher education teachers in Oyo state, Nigeria. The research adopted survey desing and three research question asked. The population for the study consisted of all the lecturers in universities in Oyo state. Multistage sampling techniques was used in this study. One federal and one state universities were purposively selected because they were the only federal and state universities in Oyo state. From each university, four faculties were randomly chosen. From each faculty four departments were randomly selected making a total of sixteen departments. 5 lecturers and 10 students were randomly chosen from each department totaling 80 lecturers and 160 students. Mode of implementating Higher Education Curriculum Scale (MIHECS) and Students' Perception of Problem Associatied with Curriculum Implementation and Possible Solution Scale (SPPCIPSS) were developed to generate data for the study. The research questions were answered using descriptive statistics. Results revealed that 25% of the lecturers always have access to the content of the curriculum, while 50% disclosed that they often do. Also, 95% of the students and 68% of the lecturers agreed thatthe lecture rooms are not conductive for the teaching-learning process while 05% of the students and 32% of the lecutrers disagreed.69% of the lecturers and 75% of the students suggested that workshops on curriculum implementation should be mounted for lecturers, while 56% of the lecturers and 88% of the students said that head of units/departments should seek for feedback from students on thier lecturer's performance. Recommendations were: workshops on curriculum implementation should be floated for lecturers at the national and state levels, while curriculum should be effectively implemented with the use of relevant instructional materials. also, lecturers and students should learn how to and indeed utilize ICT facilities to enhance teaching and learning process.